2017
DOI: 10.1186/s13104-017-2948-3
|View full text |Cite
|
Sign up to set email alerts
|

Motives for change of first-line antiretroviral therapy regimens in an unselected cohort of HIV/AIDS patients at a major referral centre in South-west Cameroon

Abstract: ObjectiveThe rapid scale-up of antiretroviral therapy (ART) coverage in sub-Saharan Africa has encountered the challenge of maintaining international clinical standards of ART utilization and change of ART regimens. In Cameroon, scarce reports have documented the motives for change of ART. This study had as objective to investigate the reasons for switch in ART through a secondary analysis and descriptive synthesis of data from a cross-sectional study at the Limbe Regional Hospital.ResultsOne hundred participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Studies reported that the majority of patients presented to the healthcare settings when the disease had become advanced (WHO clinical stage III). 11,18,19,22 In concordant to our finding, study done in Tikur Anbesa Specialized Hospital (TASH) also indicated that the mean weight of the patients during initiation of ART was 55.6(±10) kg and four-fifths of patients had a CD4 count of less 200 cells/mm 3 at the baseline. 18…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Studies reported that the majority of patients presented to the healthcare settings when the disease had become advanced (WHO clinical stage III). 11,18,19,22 In concordant to our finding, study done in Tikur Anbesa Specialized Hospital (TASH) also indicated that the mean weight of the patients during initiation of ART was 55.6(±10) kg and four-fifths of patients had a CD4 count of less 200 cells/mm 3 at the baseline. 18…”
Section: Discussionsupporting
confidence: 79%
“…In line with the present finding, several studies indicated that among patients who had their treatment changed for the first time, the majority was female. 3,4,11,18–20 This might be due to the fact that the higher proportion of female patients who initially started ART and the increased likelihood of regimen change among female for specific reasons such as pregnancy. Looking at the age distribution of patients included in various studies, the mean ages of the participants were 40.2 (±8.0) years in major referral hospital of Southwest Cameroon, 11 38.6 (±7.0) years and 36.5 (±8.9) years in health facilities of Addis Ababa, Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings have several clinical and public health implications. As seen in other studies in Africa [27,29,49], PLHIV are younger and facing the additional burden of non-communicable diseases. There is an urgent need to implement CVD prevention and management strategies in HIV-infected patients.…”
Section: Characteristicsmentioning
confidence: 54%
“…Also, despite specific WHO guidelines on how to manage such chronic conditions in PLHIV, their implementation remains challenging in most African countries. For example, recent studies are still reporting the use of stavudine‐based regimens, prescribed due to shortages of safer ART despite their association with cardiometabolic abnormalities . Furthermore, there are scarce data on the burden of dyslipidaemia, CVD and MS in HIV‐infected adults and association with ART in resource‐limited settings, including the Democratic Republic of the Congo (DRC) .…”
Section: Introductionmentioning
confidence: 99%